(untitled) (Web of Teachers: Inderscience Research, 2023)
For final control work, students are provided with 1,000 options from each subject, an option randomly sent by the system can be known by the student from 06.00 on the day of the final control exam, and the questions can be answered in the word text editor by writing *.it should be saved in pdf form and downloaded to the distance learning platform by 18.00 on the day of the exam. Step 1. You enter the distance learning platform by typing the login and password that belongs to your Network and customize the language interface to your Network